1997
DOI: 10.1007/s003300050134
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of localized giant cell tumour of the tendon sheath (MRI of localized GCTTS)

Abstract: The objective of this study was to evaluate the appearance of localized giant cell tumour of the tendon sheath (GCTTS) on unenhanced and Gd-enhanced MR images. MR images of 13 histologically proven cases of localized GCTTS were evaluated for mean size, location, homogeneity and signal intensity (SI) on both T1- and T2-weighted images, and enhancement pattern. All lesions except 1 affected young adults. On T1- and T2-weighted images, lesions showed predominantly low SI equal to or slightly higher than skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 7 publications
1
56
0
Order By: Relevance
“…The mass is hypointense on both sequences (Figure 4) (17). Uniform enhancement can be seen on post-contrast series ( Figure 5) (17,20).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mass is hypointense on both sequences (Figure 4) (17). Uniform enhancement can be seen on post-contrast series ( Figure 5) (17,20).…”
Section: Discussionmentioning
confidence: 95%
“…Typically, they are hypointense on T1-weighted images and hyperintense on T2-weighted images (17,19). MRI typically shows the giant cell tumor of the tendon sheath as a well-defined mass adjacent to or enveloping a tendon (18,20). The mass is hypointense on both sequences (Figure 4) (17).…”
Section: Discussionmentioning
confidence: 99%
“…L-GCTTS is well delineated and lobulated with an incomplete fibrous capsule; however, the tumor may exhibit variability in signal intensity on MR images. De Beuckeleer et al (4) observed that the majority of signal intensities of L-GCTTS were isointense to the signal intensities of muscle on T1WI and T2WI. Jelinek et al (16) investigated the MRI features of 9 L-GCTTS.…”
Section: Discussionmentioning
confidence: 99%
“…As magnetic resonance imaging (MRI) can be used to characterize and estimate the extent of soft tissue tumors, this imaging technique is currently the method of choice for the diagnosis of GCTTS (3). Certain studies have investigated the use of MRI for the diagnosis of L-GCTTS (3)(4)(5). However, few studies have exclusively clarified the characteristic MRI features of L-GCTTS and D-GCTTS.…”
Section: Introductionmentioning
confidence: 99%
“…The decreased signal intensity is attributable to the paramagnetic effect exerted by hemosiderin, which causes a blooming artifact on the gradient echo sequences [17,26]. GCTTS typically shows moderate to marked contrast enhancement after administration of gadolinium owing to the presence of numerous proliferative capillaries located in the collagenous stroma [5,16]. Other specific MRI features that are useful in differentiating GCTTS from malignant diagnoses, such as extraskeletal osteosarcoma Fig.…”
Section: Discussion and Treatmentmentioning
confidence: 99%